Purwarupa Light Meter Menggunakan Sensor Warna untuk Fotografi - Kumara, Alam Ega; Hendry, Jans (Jurnal Pekommas, 2024)
Light plays an important role in the photography that it affects the quality of the photos. The lighting in the photo is influenced by the three elements of Triangle Exposure, namely aperture, shutter speed, and ISO contained in the camera settings. A tool named Light Meter is a tool that can measure photographic lighting by calculating the intensity of light received by the object of the photo to then adjust the Triangle Exposure elements to get recommendations for appropriate camera settings. In this study, the light meter was implemented using an ESP32 microcontroller combined with a TCS34725 color sensor that functions to detect light intensity. The results of the TCS34725 color sensor to detect light intensity compared to the comparison lux meter AS803 obtained an eror value of 0.3 indoors and 17.2 outdoors with the addition of a dome diffuser. Based on the detected light intensity data is then used in the calculation of Triangle Exposure adjustment. The results of the implementation of the Triangle Exposure recommendation provided by the tool for camera settings show photos with a more even distribution of light and color based on histogram analysis in low light conditions.